Evaluation of a diagnostic therapeutic educational pathway for asthma management in youth. Issue 2 (19th December 2017) - Guarnaccia, Sebastiano; Quecchia, Cristina; Festa, Andrea; Magoni, Michele; Moneda, Marco; Gretter, Valeria; Scarcella, Carmelo; Pluda, Ada; Gasparotti, Cinzia; Frassine, Malica; Vitale, Luigi; D'Agata, Emanuele; et al.
Abstract: Background: In spite of some evidence for positive effects of patient's education to asthma self‐management by randomized clinical trials, there are few studies on the impact of patient' s educational programs in the real world. We aimed to assess the impact of a diagnostic therapeutic educational pathway (DTEP) on asthma control of children and adolescents by comparing frequency of outcomes indicative of asthma control before and after attending the pathway. Methods: This is a retrospective cohort study including all patients aged 6‐11 and 12‐17 years who attended the DTEP in 2007‐2014. The DTEP includes 3 specialist's evaluations at 8‐ to 12‐week intervals and two follow‐up visits. Patients and their parents receive an educational course concerning prevention measures, early recognition of symptoms, and appropriate use of drugs and devices. The rates of hospitalizations, outpatient services, emergency room visits, and drug prescriptions were considered as outcomes and computed as number of events divided by person‐time. Results: A total of 806 patients were enrolled. A statistically significant decrease in rates from before to after DTEP was observed for almost all outcomes, in both age groups, with relative risks ranging from 0.12 to 0.60. The rates of drug prescription showed a statistically significant decrease, from before to after DTEP, for each type of medicine for asthma, in both age groups, from percent difference of −66% to −24.3%. Conclusions: The positive impact of this program on the outcomes indicative of asthma control in both children and adolescents suggests that it may be valuable for asthma management. Abstract :